2016
DOI: 10.3389/fpsyg.2016.01844
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Intelligence as a Mediator of the Relationship between Executive Control and Balanced Time Perspective

Abstract: This study examined the cognitive foundations of the balanced time perspective (BTP) proposed by Zimbardo and Boyd (1999). Although BTP is defined as the mental ability to switch effectively between different temporal perspectives, its connection with cognitive functioning has not yet been established. We addressed this by exploring the relationships between time perspectives and both fluid intelligence (measured with Raven’s and Cattell’s tests) and executive control (Go/No-go and anti-saccade tasks). An inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…First, we expected that two time perspectives, Past Negative and Present Fatalism, would be associated with lower WM updating and switching (H1). Previous studies have shown that these two TPs are systematically correlated with poorer cognitive functioning (Witowska and Zajenkowski 2018;Zajenkowski et al 2016aZajenkowski et al , 2016b. Both TPs are strongly associated with negative emotionality, e.g.…”
Section: The Current Studymentioning
confidence: 90%
See 2 more Smart Citations
“…First, we expected that two time perspectives, Past Negative and Present Fatalism, would be associated with lower WM updating and switching (H1). Previous studies have shown that these two TPs are systematically correlated with poorer cognitive functioning (Witowska and Zajenkowski 2018;Zajenkowski et al 2016aZajenkowski et al , 2016b. Both TPs are strongly associated with negative emotionality, e.g.…”
Section: The Current Studymentioning
confidence: 90%
“…Furthermore, BTP was correlated with high levels of fluid intelligence and inhibition (Zajenkowski et al 2016a, b). It has been suggested that fluid ability and inhibitory control allow individuals to be less biased toward a particular time zone, especially maladaptive ones such as Past Negative and Present Fatalism (Zajenkowski et al 2016b).…”
Section: Time Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Potential common associations of mindfulness and BTP with cognitive abilities are moreover of interest. Findings that better inhibition ability is related to lower DBTP (Zajenkowski et al 2016) and is the executive component for which improvements following MBIs are most evident (Galliant 2016) are of interest at this point. Potential common neural underpinnings of the construct should be investigated further; preliminary evidence seem to suggest that both mindfulness (Tang et al 2015) and BTP (Guo et al 2017) involve increased connectivity of certain areas in the Default Mode Network.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 96%
“…As a result of a number of preliminary studies, Zimbardo and Boyd (1999) distinguished five TPs: Past Negative, reflecting a negative perception of the past; Past Positive, characterized by a sentimental perception of the past; Present Hedonistic, characterized by striving toward present pleasure and enjoyment; Present Fatalistic, related to a hopeless attitude toward the future, and Future, concentrated on future goals and rewards. One's perception of time was found to be a relatively stable individual difference trait and have been associated with affective (Stolarski et al 2014), cognitive (Zajenkowski et al 2016), and behavioral (Harber et al 2003) outcomes. There are also initial studies showing that personal Time Perspective can be modified by the therapeutic process (Sword et al 2014).…”
Section: Time Perspectivesmentioning
confidence: 98%